IN THE REALM OF FREEDOM, EQUALITY AND PROPERTY: IDEOLOGICAL ASPECTS OF HUMAN RIGHTS - Jovanovic, Andrea (Political Review, 2023)
This paper deals with the question of ideological characteristics of human rights by using conceptual and critical–historical analysis. It first examines the different ideological conceptions of human rights by analyzing them from three distinct conceptions of ideology: critical, neutral, and functionalistic. It then proceeds to the critique of the neutral and functionalist conceptions and advocates instead for the critical conception as the most fruitful analytical frame. It concludes that the critical approach is the most suitable for explaining the complexity of the phenomenon of human rights as ideology, including their contradictions but also their emancipatory potential within and beyond the capitalist social and economic system.